Electrohydrodynamic jet printed silver-grid electrode for transparent raindrop energy-based triboelectric nanogenerator. (May 2022) - Im, Busi; Lee, Seoung-Ki; Kang, Giho; Moon, Joonkyeong; Byun, Doyoung; Cho, Dae-Hyun
Abstract: A transparent water-solid contact triboelectric nanogenerator (TENG) integrated with a solar cell is expected to be a reliable source of stable energy during both dry and wet seasons. This is particularly significant in countries with tropical climates, where both seasons are pronounced. In this paper, a highly transparent and conductive electrohydrodynamic jet-printed Ag nanoparticle (NP) electrode-based TENG (PA-TENG) was developed and integrated with a solar cell. The fabricated PA-TENG exhibited a maximum power output of 1.17 W/m 2, and average and maximum optical transmittance of 91% and 96%, respectively. The conventional indium tin oxide (ITO) electrode was selected to serve as a control group. ITO-TENG exhibited maximum and average optical transmittances of 92% and 88%, respectively. In addition, its power output was approximately three times lower than that of PA-TENG. This performance improvement of PA-TENG is attributed to the effective charge-inducing ability caused by the high contact barrier at the AgNP/polydimethylsiloxane (PDMS) interface as well as the high conductivity of the printed AgNP electrode (sheet resistance: 3.6 Ω/sq). We also find that the PA-TENG exhibits the highest transparency and power output among the reported data of the transparent water-solid contact TENG. Finally, integration of the solar cell within PA-TENG reduced its power density by 3.6% while it reduced that of ITO-TENG by 5.2%. This indicates that PA-TENG is more suitable for integration with a solar cell than ITO-TENG on both rainy and sunny days. By estimating the loss in electricity in the solar cell induced by the opacity of PA-TENG and the electricity generated by it, we concluded that PA-TENG integrated with a solar cell could serve as a potential source of stable eco-friendly energy in regions with a tropical wet-dry climate. Graphical Abstract: ga1 Highlights: The EHD jet-printed Ag-grid electrode exhibits high transparency and conductivity. High-performance raindrop energy-based TENG is developed with the printed Ag-grid. Enhanced contact barrier at the AgNP/PDMS causes effective charge recombination. The high conductivity of Ag-grid increases induced charges at the AgNP/PDMS. The developed TENG has great potential in a hybrid nanogenerator with a solar cell.